Ghrelin Selectively Inhibits CaV3.3 Subtype of Low-Voltage-Gated Calcium Channels - Mustafá, Emilio Román (2020)
The mechanisms by which ghrelin controls electrical activity in the hypothalamus are not fully understood. One unexplored target of ghrelin is CaV3, responsible for transient calcium currents (T-currents) that control neuronal firing. We investigated the effect of ghrelin on CaV3 subtypes and how this modulation impacts on neuronal activity. We performed whole-cell patch-clamp recordings in primary mouse hypothalamic cultures to explore the effect of ghrelin on T-currents. We also recorded calcium currents from transiently transfected tsA201 cells to study the sensitivity of each CaV3 subtype to GHSR activation. Finally, we ran a computational model combining the well-known reduction of potassium current by ghrelin with the CaV3 biophysical parameter modifications induced by ghrelin to predict the impact on neuronal electrical behavior. We found that ghrelin inhibits native NiCl₂ sensitive current currents in hypothalamic neurons. We determined that CaV3.3 is the only CaV3 subtype sensitive to ghrelin. The modulation of CaV3.3 by ghrelin comprises a reduction in maximum conductance, a shift to hyperpolarized voltages of the I–V and steady-state inactivation curves, and an acceleration of activation and inactivation kinetics. Our model-based prediction indicates that the inhibition of CaV3.3 would attenuate the stimulation of firing originating from the inhibition of potassium currents by ghrelin. In summary, we discovered a new target of ghrelin in neurons: the CaV3.3. This mechanism would imply a negative feed-forward regulation of the neuronal activation exerted by ghrelin. Our work expands the knowledge of the wide range of actions of GHSR, a receptor potentially targeted by therapeutics for several diseases.